Study on the Treatment of Veterinary Antibiotic Wastewater by Advanced Oxidation Synergized with Biofilm - Park, Jeffrey; Sofy, Narwa; Awads, Irina (Journal of Green Energy and Environmental Engineering, 2025)
The discharge of veterinary antibiotics into natural water bodies can lead to the spread of environmental antibiotic resistance genes, disrupt ecological balance, and pose threats to human health. This study employed advanced oxidation technology synergized with biofilm to conduct in-depth treatment research on production wastewater containing two veterinary antibiotics, Tylosin (TYL) and Tylvalosin (TAT), and investigated the degradation characteristics of TYL and TAT by advanced oxidation technology. The results showed that the degradation efficiency of ozone (O₃) was significantly superior to that of hydrogen peroxide (H₂O₂) and sodium chlorite (NaClO₂). Under acidic conditions (pH=5), the degradation rates of TYL and TAT by O₃ exceeded 92% within 3 minutes. Kinetic analysis confirmed that the oxidative degradation process of TYL and TAT by O₃ followed a pseudo-first-order kinetic model. Based on the characteristics of the actual wastewater from the enterprise, a pilot-scale device integrating "ozone oxidation + biofilm + anaerobic/aerobic + coagulation sedimentation" was constructed. After debugging and biofilm acclimation, a continuous 10-day treatment trial using simulated wastewater demonstrated significant wastewater treatment effectiveness by this system. The degradation rates for TYL and TAT reached 97.1% and 95.8%, respectively; the degradation rates for COD and BOD₅ both exceeded 98%; and the degradation rate for NH₃-N was 88.6%.